User Behavior on Actual Use of Academic Information System in Makassar State University: Is Information Technology Facilities Have a Moderating Role to Strengthen the Behavior? - Aris, Valentino; Alam, Syamsu; Aris, Arini Lestari (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to determine factors that influence the use of information technology in higher education, especially at Makassar State University. The type of information technology studied is academic information systems. This study combines two theories, namely the Technology Acceptance Model (TAM) and The Theory of Planned Behavior (TPB) to explain the user behavior for the use of academic information systems at Makassar State University. The results of this study indicate that perceived usefulness and ease of use significantly affect user behavioral intention to use academic information systems. Behavioral intention significantly affected actual use of the academic information system. An interesting finding is that the facilities available for the use of the system in the campus environment have no significant effect on the use of the academic information system at Makassar State University.